The Growth and Efficiency of Public Spending (Book). - Brief, Richard P.; Nunamaker, Thomas R. (The Accounting Review, 1988)
Reviews the book "The Growth and Efficiency of Public Spending," by M.S. Levitt and M.A.S. Joyce.